The Meaning of Grave Pilgrimage: A Phenomenological Study at the Tomb of Syekh Wasil Kediri - Endris Kirana Zahra; M. Thoriqul Huda (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Grave pilgrimage is something that we often encounter and maybe even do since childhood. This tradition aims to visit the graves of people we want to pray for, such as grandparents to great-grandparents, to visit the graves of figures who have no special pedigree with us, such as kyai and scholars and guardians, even village elders who are considered sacred and can bring blessings to those who follow the pilgrimage tradition. The author takes data using phenomenological studies because the grave pilgrimage is a phenomenon for society. Especially for Javanese people who nobly respect tombs and pesarean more than other communities. In such a place, Javanese people must follow the existing rules and manners. The author views that the phenomenon of grave pilgrimage is closely related to the cultural system of the community, which is carried out with different motivations. In this paper, the author takes data from the phenomenon of grave pilgrimage at the grave of Syekh Wasil, Kediri City. Syekh Wasil is seen not only as a charismatic figure whose grave is visited by many Muslims but also because he is a symbol of the process of spreading Islam in Java, especially in the area of the Kediri Kingdom.